PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KECERDASAN EMOSIONAL, DAN PEMBERDAYAAN KARYAWAN TERHADAP KEPUASAN KERJA KARYAWAN - Maryanti, Luh Deni; Dewi, I Gusti Ayu Manuati (E-Jurnal Manajemen, 2016)
This study aims to analyze the effect of transformational leadership, emotional intelligence, and employee empowerment on employee job satisfaction. The location of this research is in the Credit Institutions Desa Adat Pecatu. The population in this study were all employees of Credit Institutions Desa Adat Pecatu totaling 52 people , and not among the leaders. The sampling method in this research is saturated sampling , where all populations as respondents and not among the leaders . The analysis tool used is multiple linear regression. The results obtained in this study is transformational leadership and significant positive effect on job satisfaction, emotional intelligence and significant positive effect on job satisfaction, and employee pemberdayaa positive and significant effect on job satisfaction. This study has several limitations of the present study only look at that job satisfaction can be created by a factor of transformational leadership, emotional intelligence, and employee empowerment, but does not rule out the emergence of other factors outside of the study.
Keywords: transformational leadership, emotional intelligence, employee empowerment, job satisfaction